CHANGES IN AGRICULTURAL LAND USE TO NON-AGRICULTURAL LAND IN GROGOL DISTRICT OF SUKOHARJO REGENCY IN 2001 - 2018 - Muh. Husyain Rifai; Bayu Kurniawan Nugroho; Ary Wijayanti (Universitas Veteran Bangun Nusantara, 2021)
This research was conducted in Grogol Sub-District of Sukoharjo Regency. This research aims to: (1) find out the land use in Grogol Sub-District in 2001 and 2018 (2) to find out the changes in land use in Grogol Sub-District in 2001 - 2018. The methods used in this study are: (1) using the land use map in 2001 obtained from the Indonesian Earth View Map (RBI), while the land use map in 2018 was obtained from digitization of Quickbird satellite imagery published from Maxar Technologies by regulating the year of publication on September 05, 2018. (2) overlay method isused todetermine land use changes in 2001-2018. The results obtained in this study are the land use of Grogol Sub-District in 2001 covering an area of 3,116 hectares which includes 1,718 hectares of rice fields, 1,242 hectares of residential land, and 156 hectares of vacant land. Meanwhile, land use in Grogol Sub-District in 2018 was 3,116 hectares which includes 1,230 hectares of rice fields, 1,816 hectares of residential land, and 70 hectares of vacant land. The change in land use of Grogol Sub-District in 2001 - 2018 amounted to 1,186 hectares and the area of land that was not changed by 1,930 hectares. Grogol sub-district in 2001 and 2018 the pattern of land use change is elongated following the road, elongated following the river, and radial (thorough).